Involvement of the Global Regulator GlxR in 3-Hydroxybenzoate and Gentisate Utilization by Corynebacterium glutamicum - Chao, Hongjun (American Society for Microbiology, 2014)
Corynebacterium glutamicum is an industrially important producer of amino acids and organic acids, as well as an emerging model system for aromatic assimilation. An IclR-type regulator GenR has been characterized to activate the transcription of genDFM and genKH operons for 3-hydroxybenzoate and gentisate catabolism and represses its own expression. On the other hand, GlxR, a global regulator of the cyclic AMP (cAMP) receptor protein-fumarate nitrate reductase regulator (CRP-FNR) type, was also predicted to be involved in this pathway. In this study, electrophoretic mobility shift assays and footprinting analyses demonstrated that GlxR bound to three sites in the promoter regions of three gen operons. A combination of site-directed mutagenesis of the biding sites, promoter activity assay, and GlxR overexpression demonstrated that GlxR repressed their expression by binding these sites. One GlxR binding site (DFMx) was found to be located −13 to +8 bp upstream of the genDFM promoter, which was involved in negative regulation of genDFM transcription. The GlxR binding site R-KHx01 (located between positions −11 to +5) was upstream of the genKH promoter sequence and involved in negative regulation of its transcription. The binding site R-KHx02, at which GlxR binds to genR promoter to repress its expression, was found within a footprint extending from positions −71 to −91 bp. These results reveal that GlxR represses the transcription of all three gen operons and then contributes to the synchronization of their expression for 3-hydroxybenzoate and gentisate catabolism in collaboration with the specific regulator GenR.